Axially Asymmetric Steady State Model of Jupiter's Magnetosphere‐Ionosphere Coupling. Issue 11 (29th October 2021) - Pensionerov, I. A.; Cowley, S. W. H.; Belenkaya, E. S.; Alexeev, I. I.
Abstract: We present an axially asymmetric steady state model of Jupiter's magnetosphere‐ionosphere coupling with variable ionospheric conductivity dependent on the field‐aligned current density. We use Juno and Galileo data to construct a simple model of the equatorial magnetic field, and develop a method for solving the system of partial differential equations describing magnetosphere‐ionosphere coupling. Using this model, we study the behavior of the system with different radial mass transport rates of magnetospheric plasma and the effect of additional field‐aligned currents associated with Jupiter's nightside partial ring current. We compare the model magnetodisc current intensities with those determined directly from magnetic field measurements in various local time sectors, and find that the value of mass transport rate of 2, 000 kg  s − 1, larger than usually estimated, better accounts for the observed radial currents. We also find that the inclusion of field‐aligned currents associated with Jupiter's partial ring current helps to explain the local time variation of the radial currents, reducing the discrepancy between the model and the observations. Plain Language Summary: One of the key processes in Jupiter's magnetosphere is the transfer of angular momentum from the planet to the magnetospheric plasma. It is a primary source of energy in the magnetosphere and is thought to be one of the main drivers of the auroral emissions. It was extensively studied using stationary force‐balance models. As an approximation, these models assumed axial symmetry, but due to the solar wind influence the structure of Jupiter's magnetosphere is different depending on local time. We present an improved model which partially accounts for this asymmetry. We use it together with Juno and Galileo spacecraft magnetic field measurements to study angular momentum transport at different local times. We found that the observations suggest an approximately twice larger plasma production rate by the moon Io, than is usually estimated. We also show how the asymmetries in the equatorial magnetospheric current can affect the angular momentum transfer. Key Points: We develop an axially asymmetric model of Jovian magnetosphere‐ionosphere coupling Comparison of model calculations with observed magnetodisc radial currents suggests an average radial mass transport rate of ∼2, 000 kg/s Inclusion of a nightside partial ring current helps to explain the local time variation of the radial currents